Adenosine: a sensitive marker of myocardial ischaemia in man - Bardenheuer, Hubert J.; Fabry, Andrea; Höfling, Berthold; Peter, Klaus (Cardiovascular research, 1994)
Objective: In the human heart, the significance of adenosine as an indicator of myocardial ischaemia is controversial. Since adenosine fulfils key functions in the regulation of cardiac metabolism, its sensitivity as a marker of tissue ischaemia was investigated in this study in relation to other metabolites such as hypoxanthine and lactate. Methods: Cardiac metabolite production was studied in 18 patients with left coronary obstruction (>90%) undergoing percutaneous transluminal coronary angioplasty (PTCA). Three balloon inflation procedures per patient were performed for 30, 60, and 90 s (±5 s each) and coronary sinus adenosine, hypoxanthine, uric acid, and lactate were determined. Results: Before PTCA, coronary sinus concentrations of adenosine and hypoxanthine were 176(SEM 34) and 723(73) nM, respectively, and the lactate concentration was 0.47(0.07) mM. Lactate was extracted by cardiac tissue during normoxia, and adenosine and hypoxanthine were in the physiological range of healthy volunteers. During reperfusion the concentrations of all myocardial metabolites were temporarily increased. In particular, adenosine was enhanced in close proportion to the duration of coronary occlusion. Moreover, coronary sinus adenosine, but not lactate, was significantly lowered during reperfusion when nifedipine (0.2 mg) was given by intracoronary injection before PTCA. Conclusions: With longer periods of coronary occlusion (>30 s) the relative rank order of sensitivity indicating myocardial ischaemia was adenosine > lactate > hypoxanthine > uric acid. Coronary sinus concentrations of adenosine are quantitatively sufficient to be responsible for some of the changes in coronary blood flow occuring during reactive hyperaemia.Cardiovascular Research 1994;28:656-662